Residual strength of blended cement pastes and mortar exposed to elevated temperatures - Lee, H.; Vimonsatit, Vanissorn; Chindaprasirt, P. (E J S E International Ltd., 2016)
This paper presents the outcome of a series of tests to determine properties of blended cement pastes and mortar mixtures using Taguchi's design of experiment approach. Fly ash (FA), water to cementitious material ratio (w/c), superplasticiser (SP) and sand to cementitious material ratio (s/c) are the main parameters considered. Mixture samples were tested at varying temperatures up to 800oC. The ANOVA results and regression analysis show that an increase in FA content and w/c ratio lead to a decrease in the density of blended cement. For compressive strength development, an increase in FA content and s/c ratio decreased the compressive strength development. Within the tested levels of the parameters, the optimum mix to achieve the highest compressive strength of blended cement mixtures is 20% of FA content, 1.5 of s/c ratio, 0.35 of w/c ratio and 0.2% of SP. Increasing the content of FA and SP improved the overall residual strength, and the optimum mix design to achieve the highest residual strength is 20% of FA, 1.5 of s/c ratio, 0.35 of w/c ratio and 0.2 of SP. Based on all the test results, an empirical formula for predicting residual strength of blended cement paste and mortar is proposed.